Smart tourist destinations: an analysis of tourism governance in Búzios - Cid Bárcia, Liana (2024)
In the 1990s the term smart city came up, whose meaning is attached to urban development.From this term, the concept of smart tourism destinations was developed, which are destinationscapable of bringing more innovation, competitivity, improved quality of life and tourist experiencein a territory. For these benefits to happen, it is necessary that the place receive investments mainlyin the fields of sustainability and information technology and communication. Besides, companies,residents and local governance must be engaged in the process of transforming a destination intoa smart one, according to certification criteria defined by the Ministry of Tourism. In 2011, theenergy company Ampla/Enel started the Búzios Intelligent City project, aimed at improving theelectricity grid to make the city smart. In 2016 the project was closed and Búzios did not become in-telligent for some reasons, such as lack of involvement of local actors and changes in the municipal-ity’s governance. From this context, this research sought to identify how tourism governance canhelp a tourist destination to become intelligent. Besides the bibliographical research, we analyzeddocuments about the Búzios Intelligent City Project, minutes of meetings of the Búzios MunicipalTourism Council, internal regulations and interviews with parties related to this council.